MANAJEMEN KOMPLAIN DALAM PELAYANAN PUBLIK DI PERUSAHAAN LISTIRIK NEGARA (PLN) - Jemma, Jemma; Parawu, Hafiz Elfiansyah; Taufik, Ahmad (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
This research aims to determine and analyze the implementation of complaint management carried out by ULP PLN Panakkukang towards customers. The method used in this research is a descriptive qualitative method. Data collection techniques involve observation, interviews, and documentation. The results of this research show that the complaint management indicators implemented at ULP PLN Panakkukang, such as the speed of the complaint process, complaint handling, and ease of filing complaints, have met or even exceeded customer expectations. However, the volume of complaints is still significant, indicating the need for ULP PLN Panakkukang to carry out performance evaluations to prevent errors that could trigger complaints from customers.